Tahfiz Psychogeography Of The Marginals: Reimagining Self And Place Through Narratives - Mohd Muzhafar Idrus; Normazla Ahmad Mahir; Habibah Ismail; Noornajihan Ja‘afar (National University of Malaysia Press, 2024)
Indexed by MyCite